2007
DOI: 10.1080/17486020701377124
|View full text |Cite
|
Sign up to set email alerts
|

Stress non-uniformity in a hollow cylinder torsional sand specimen

Abstract: Abstract. The hollow cylinder torsional apparatus (HCTA) facilitates more generalized stress path testing although it has been criticized on account of the level of stress nonuniformity that may develop due to the curvature of the test specimen walls. The stress nonuniformity that may develop in dense sand specimens (35.5-mm inner radius, 50.0-mm outer radius and 200-mm in height) over small-to-medium strain levels in the HCTA were studied using an isotropic linear-elastic stress analysis. The stress nonunifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…This may be done in directional shear or in torsion shear equipment with different pressures applied inside and outside the hollow cylinder specimen. Limited and sporadic experimental results have been provided in this respect by Arthur and Menzies (1972), Arthur and Phillips (1975), Hight et al (1983), Miura et al (1986), Pradel et al (1990), O'Kelly (2007), O'Kelly andNaughton (2009) and by Chairo et al (2013). While these studies indicated some variation in the friction angle, none provided a complete picture.…”
Section: Previous Studies Of Cross-anisotropymentioning
confidence: 81%
“…This may be done in directional shear or in torsion shear equipment with different pressures applied inside and outside the hollow cylinder specimen. Limited and sporadic experimental results have been provided in this respect by Arthur and Menzies (1972), Arthur and Phillips (1975), Hight et al (1983), Miura et al (1986), Pradel et al (1990), O'Kelly (2007), O'Kelly andNaughton (2009) and by Chairo et al (2013). While these studies indicated some variation in the friction angle, none provided a complete picture.…”
Section: Previous Studies Of Cross-anisotropymentioning
confidence: 81%
“…Numerical analysis by Naughton and O'Kelly (2007) indicated that the stress non-uniformity that may develop across the thickness of the UCD specimen due to its wall curvature increased in proportion to the major-to-minor principal stress ratio (R), although the level of stress non-uniformity was generally acceptable throughout the stress space for R  1.5. The specimen wall thickness of 14.5 mm was also sufficiently large in relation to the grain size of the sand so that a uniform densification of the specimen could be achieved during specimen preparation and potential failure mechanisms were free to develop during the stress path tests.…”
Section: Overview Of Apparatusmentioning
confidence: 99%
“…(Table 1) induced across the specimen wall thickness were derived from equilibrium considerations assuming an isotropic, linear-elastic response (Naughton and O'Kelly, 2007). The stress components were integrated over the full specimen volume in order to account for the effects of the specimen wall curvature.…”
Section: Principle Of Hollow Cylinder Torsional Testingmentioning
confidence: 99%
“…The non-zero stress equations have been reported in detail by O'Kelly and Naughton (2005a,b,c) and Naughton and O'Kelly (2007). The mean non-zero strain components are calculated from the local radial (u o , u i ), axial (w) and twist () deformations measured using the proximity transducers and the inclinometers Andover an axial gauge length, L z (Eqs.…”
Section: Calculation Of Strain Responsementioning
confidence: 99%
“…Local instrumentation measures the polar deformation response over the uniformly stressed zone within the mid-third of the specimen length in the UCD HCA (Naughton and O'Kelly 2007). It is convenient to use a polar coordinate system in considering the states of stress and the deformation/strain response.…”
Section: Measurement Of Deformation Response In Ucd Hcamentioning
confidence: 99%